2012
DOI: 10.1111/j.1467-7679.2012.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Paris in Bogotá: The Aid Effectiveness Agenda and Aid Relations in Colombia

Abstract: This article uses an aid‐relationships perspective to explore the application of the Paris Declaration on Aid Effectiveness in Colombia. It argues that aid donors were subjected to an attempt to push them (back) into a technocratic corner, and that social actors' advocacy outcomes were put under threat. Both are worrying developments in a politically complex context marked by internal armed conflict and human‐rights abuses. Analysis of the Colombia case offers some useful insights into applying the Paris Decla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…] between government and donors, where the locus is international, which is quite different from national or country ownership where the main locus would be an interaction amongst government and people' (Hayman, 2009a, p. 597). By way of contrast, Rosemary McGee and Heredia (2012) found that the Colombian government used the Paris principles of ownership and alignment to justify controversial policies and decrease the influence of donors and both international and domestic NGOs. The different result in the Colombian case could be due to the government's stronger state capacity, its lesser dependence on aid or its pre-existing strong bargaining position vis-à-vis international actors.…”
Section: Donors Commit Tomentioning
confidence: 99%
“…] between government and donors, where the locus is international, which is quite different from national or country ownership where the main locus would be an interaction amongst government and people' (Hayman, 2009a, p. 597). By way of contrast, Rosemary McGee and Heredia (2012) found that the Colombian government used the Paris principles of ownership and alignment to justify controversial policies and decrease the influence of donors and both international and domestic NGOs. The different result in the Colombian case could be due to the government's stronger state capacity, its lesser dependence on aid or its pre-existing strong bargaining position vis-à-vis international actors.…”
Section: Donors Commit Tomentioning
confidence: 99%